MENTAL IMAGERY. A TOOL TO PROMOTE CREATIVITY IN THE FL CLASSROOM - Ávila López, Francisco Javier (ELIA: Estudios de Lingüística Inglesa Aplicada, 2017)
Abstract Recent psychological research suggests that much of our of learning includes imagery as part of the cognitive processes. Mental imagery can lead to significant improvement in learning given proper guidance. One of the most important reasons for that cognitive potential is the close relationship between mental imagery and creativity. Research points to the ability to generate and manipulate mental imagery as one of the main components of creativity; guided mental imagery training can help to awaken a sense of creativity atrophied by an educational system that focuses mainly on concepts and numbers. After discussing the relationship between mental imagery and creativity, a number of activities for the FL classroom are proposed and analyzed.